Pregnancy and Evans´syndrome: Case report - Artucio, Santiago (2015)
Evans´ syndrome is the coexistence of autoimmune thrombocytopenia with autoimmune hemolytic anemia. It is rarely found during the course of a pregnancy. This makes treatment options more difficult, since some therapeutic drugs are teratogenic. The effects of Evans´ syndrome in the fetus and newborn are unknown given the low number of reported cases. We report the case of a patient with preconceptional diagnosis of Evans' syndrome, who develops a hemolytic crisis during the course of a pregnancy, and diagnosis of intrauterine growth restriction (IUGR), treated at Clínica Ginecotocológica "A" at the Pereira Rossell Hospital Center, in Montevideo, Uruguay. Treatment options and evolution are analyzed, as well as previous reports.